2022
DOI: 10.34133/2022/9826279
|View full text |Cite
|
Sign up to set email alerts
|

Particle-Mediated Histotripsy for the Targeted Treatment of Intraluminal Biofilms in Catheter-Based Medical Devices

Abstract: Objective. This paper is an initial work towards developing particle-mediated histotripsy (PMH) as a novel method of treating catheter-based medical device (CBMD) intraluminal biofilms. Impact Statement. CBMDs commonly become infected with bacterial biofilms leading to medical device failure, infection, and adverse patient outcomes. Introduction. Histotripsy is a noninvasive focused ultrasound ablation method that was recently proposed as a novel method to remove intraluminal biofilms. Here, we explore the pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…For most volumetric ablation histotripsy applications, such as targeting large tumors (Schuster et al 2018, Ruger et al 2022, Vidal-Jove et al 2022, the predictable changes in the bubble cloud size and location shown in this study are not to be expected to deter the use of high PRFs, as long as these changes are integrated into volumetric ablation delivery methods. However, for high-precision treatments such as histotripsy thrombolysis (Maxwell et al 2009, Maxwell et al 2011a, Hendley et al 2022 or biofilm ablation in medical catheters (Childers et al 2022), these changes in bubble cloud activity may have more significant effects that could limit the maximum PRF for those applications. Therefore, further investigation may be warranted to improve repeatability and predictability for ultra-high PRF treatments when applied for high-precision applications.…”
Section: Discussionmentioning
confidence: 99%
“…For most volumetric ablation histotripsy applications, such as targeting large tumors (Schuster et al 2018, Ruger et al 2022, Vidal-Jove et al 2022, the predictable changes in the bubble cloud size and location shown in this study are not to be expected to deter the use of high PRFs, as long as these changes are integrated into volumetric ablation delivery methods. However, for high-precision treatments such as histotripsy thrombolysis (Maxwell et al 2009, Maxwell et al 2011a, Hendley et al 2022 or biofilm ablation in medical catheters (Childers et al 2022), these changes in bubble cloud activity may have more significant effects that could limit the maximum PRF for those applications. Therefore, further investigation may be warranted to improve repeatability and predictability for ultra-high PRF treatments when applied for high-precision applications.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore likely that robotically guided histotripsy systems will need to be developed for precise targeting of catheter biofilms, similar to the systems in development for precise tumor ablation [36−38]. Another approach to address this challenge is the use of particle-mediated histotripsy (PMH) methods, which have recently been explored by our group [39]. PMH shows great promise in producing a treatment modality that is easily targetable using a handheld transducer.…”
Section: Discussionmentioning
confidence: 99%
“…PMH shows great promise in producing a treatment modality that is easily targetable using a handheld transducer. In the PMH process, fluid-filled or gas-filled particles reduce the histotripsy cavitation threshold [40,41], allowing for histotripsy to be applied to the catheter lumen without the need for image-guided techniques [39]. This property of PMH could allow for the rapid treatment of catheter biofilms by use of a less focused transducer that can cover a larger portion of the catheter at a single time using a simple handheld device.…”
Section: Discussionmentioning
confidence: 99%
“…The use of microbubbles has been well established over the past decades and its potential applications such as medical treatment [1] , [2] , [3] , waste water treatment [4] , food sterilization [5] , etc. has been extensively explored [6] .…”
Section: Introductionmentioning
confidence: 99%